2019
DOI: 10.1007/jhep12(2019)145
|View full text |Cite
|
Sign up to set email alerts
|

On supersymmetry breaking vacua from D-branes at orientifold singularities

Abstract: We present a large class of models of D-branes at (orientifold) Calabi-Yau singularities which enjoy dynamical supersymmetry breaking at low energy, by means of either the SU (5) or 3-2 supersymmetry breaking models. Once embedded in a warped throat or, equivalently, in a large N theory, all models display an instability along a Coulomb branch direction towards supersymmetry preserving vacua. Interestingly, the nature of the runaway mechanism is model-independent and has a precise geometrical interpretation. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(54 citation statements)
references
References 52 publications
5
49
0
Order By: Relevance
“…In this same work [18], however, by generalizing previous results of [16], it was shown that in the decoupling limit [1], in which the DSB fractional D-brane bound state becomes part of a UV complete large N D-brane model and gravity is decoupled, all models display an instability. This instability turned out to have a common, model-independent geometric origin in terms of N = 2 fractional branes probing the singularity.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In this same work [18], however, by generalizing previous results of [16], it was shown that in the decoupling limit [1], in which the DSB fractional D-brane bound state becomes part of a UV complete large N D-brane model and gravity is decoupled, all models display an instability. This instability turned out to have a common, model-independent geometric origin in terms of N = 2 fractional branes probing the singularity.…”
Section: Introductionsupporting
confidence: 65%
“…This originated from [17] where an existence proof for a possibly stable DSB model obtained by considering fractional branes at orientifold singularities was given. These results were generalized in [18], where it was shown that a large class of orientifolds admit fractional D-brane configurations realizing some of the most popular and simple DSB models, namely the incalculable SU (5) [19] and/or 3-2 [20] models.…”
Section: Introductionmentioning
confidence: 92%
“…with deformation parameter such that we have dP = P = 0 on the locus x = y = u = v = 0 in the singular limit → 0. Here, 34) and (x 0 4 , x 0 6 ) is a solution to eq. (4.23).…”
Section: The Greene-plesser Mirror Dualmentioning
confidence: 99%
“…with deformation parameter such that we have dP = P = 0 on the locus x = y = u = v = 0 in the singular limit → 0. Here, 34) and (x 0 4 , x 0 6 ) is a solution to Equation (4.23). Here, := 1 + 6 − 7 , and we neglect higher-order corrections in (x, y, u, v) as well as non-constant terms that vanish in the limit → 0.…”
Section: The Greene-plesser Mirror Dualmentioning
confidence: 99%